2013
DOI: 10.1016/j.aju.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The venous drainage of the corpora cavernosa in the human penis

Abstract: ObjectiveTo study the drainage proportions from the corpora cavernosa in defrosted human cadavers, as the veins related to penile erection were recently depicted to comprise the deep dorsal vein (DDV), a pair of cavernous veins (CVs) and two pairs of para-arterial veins (PAVs), as opposed to a single DDV between Buck’s fascia and the tunica albuginea of the human penis.Materials and methodsWith no formalin fixation, 10 defrosted male human cadavers were used for this study. After injecting a 10% solution of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…In addition to histology confirmation, interestingly, grossly, livor mortis at either the groin or medial thigh can disappear once the perfusion amount of 10% colloid exceeds 350 mL. 21 Thus, this hemodynamic model is likely to mimic the human physiological status, and the infusion colloid is valid as well. Thirty seconds were adequate to close the venous lumen, which was exhibited as a hemostatic status for homeostasis clinically.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to histology confirmation, interestingly, grossly, livor mortis at either the groin or medial thigh can disappear once the perfusion amount of 10% colloid exceeds 350 mL. 21 Thus, this hemodynamic model is likely to mimic the human physiological status, and the infusion colloid is valid as well. Thirty seconds were adequate to close the venous lumen, which was exhibited as a hemostatic status for homeostasis clinically.…”
Section: Discussionmentioning
confidence: 93%
“…Continuous blood flow within the venous drainage pathway in the erect state is direct evidence for the diagnosis of penile venous leak. There are superficial, middle, and deep layers of the drainage system in the penile vein . The superficial veins course between the Colles fascia and the Buck fascia, are incorporated into a superficial dorsal vein at the back of the penis, and finally drain into the great saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…In China, Criterion C is usually used, which is consistent with Criterion A or B, except for the standard of RI less than 0.80. Some studies also suggested RI less than 1 as one of the standards. However, RI in these studies was usually measured 5 to 10 minutes after the drug injection.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion for drainage of corpora cavernosa through DDV, cavernosal veins and PAVs are 60.5% (range 50.3-69.7%), 11.9% (range 5.8-22.9%) and 11.4% (range 5.2-15.0%) on their own. 24…”
Section: Penile Anatomymentioning
confidence: 99%
“…Both the medial and lateral PAVs might channel into the DDV or the Santorini’s plexus alone at the level of the infrapubic angle. The proportion for drainage of corpora cavernosa through DDV, cavernosal veins and PAVs are 60.5% (range 50.3–69.7%), 11.9% (range 5.8–22.9%) and 11.4% (range 5.2–15.0%) on their own …”
Section: Introductionmentioning
confidence: 99%